A toolbox for volumetric visualization of light properties. (October 2019) - Kartashova, T; de Ridder, H; te Pas, SF; Pont, SC
In this paper, we introduce a toolbox for the perceptually based visualization of light in a volume, focusing on the visual effects of illumination. First, our visualizations extend the conventional methods from a two-dimensional representation on surfaces to the whole volume of a scene. Second, we extend the conventional methods from showing only light intensity to visualizing three light properties (mean illuminance, primary direction and diffuseness). To make our methods generally available and easily accessible, we provide a web-based tool, to which everybody can upload data, measured by a cubic or simple illuminance meter or even a smartphone-app, and generate a variety of three-dimensional visualizations of the light field. The importance of considering the light field in its full complexity (and thus as a three-dimensional vector field instead of its two-dimensional sections) is widely acknowledged. Our toolbox allows easy access to sophisticated methods for analysing the spatial distribution of light and its primary qualities as well as how they vary throughout space. It is our hope that our results raise interest in 'third stage' approaches to lighting research and design, and the toolbox offers a practical solution to this complex problem.